The Impact of Digital Knowledge Management on Tax Compliance Efficiency: An Empirical Study of the General Tax Authority - Mohammed Hasan Abdulameer Al-Rubaye; Ali Hussein Khichari Al-Ta'I (Tikrit Journal of Administrative and Economic Sciences, 2023)
This paper investigates the relationship between knowledge management processes and tax efficiency in the context of tax administration organizations. A sample of 52 employees from the Federal Taxation Bureau was selected using stratified random sampling. Data were collected through a structured questionnaire examining various aspects of knowledge management processes, including knowledge acquisition, organization, and transfer, as well as tax efficiency indicators, such as compliance and effectiveness.